2021
DOI: 10.1001/jamanetworkopen.2021.40202
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Public Stigma of Mental Illness in the US, 1996-2018

Abstract: IMPORTANCE Stigma, the prejudice and discrimination attached to mental illness, has been persistent, interfering with help-seeking, recovery, treatment resources, workforce development, and societal productivity in individuals with mental illness. However, studies assessing changes in public perceptions of mental illness have been limited. OBJECTIVETo evaluate the nature, direction, and magnitude of population-based changes in US mental illness stigma over 22 years. DESIGN, SETTING, AND PARTICIPANTS This surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(120 citation statements)
references
References 38 publications
5
111
1
3
Order By: Relevance
“…Students in the sample had a moderately high and high endorsement of persons with a mental illness diagnosis’ dangerousness to others (31%) and to oneself (75%), respectively. The stigma endorsement found in our sample may be attributed to the higher representation of students who have previously engaged in treatment, the use of stigma measures that were nonspecific to mental illness condition, or the real occurrence of lower stigma endorsement by younger U.S. cohorts (Pescosolido et al, 2021). While we were unable to assess these issues in our study, future studies of the concurrent representation of these seven public stigma dimensions and their components on university campuses should take them into account…”
Section: Resultsmentioning
confidence: 86%
“…Students in the sample had a moderately high and high endorsement of persons with a mental illness diagnosis’ dangerousness to others (31%) and to oneself (75%), respectively. The stigma endorsement found in our sample may be attributed to the higher representation of students who have previously engaged in treatment, the use of stigma measures that were nonspecific to mental illness condition, or the real occurrence of lower stigma endorsement by younger U.S. cohorts (Pescosolido et al, 2021). While we were unable to assess these issues in our study, future studies of the concurrent representation of these seven public stigma dimensions and their components on university campuses should take them into account…”
Section: Resultsmentioning
confidence: 86%
“…This is consistent with a systematic review of school-based stigma interventions which concluded that there is insufficient evidence to suggest that such interventions are efficacious for school-age (i.e., younger) populations (Mellor, 2014). Interestingly, recent evidence indicates a pattern of decline in behavioral stigma around depression in the United States, and that the effect is attributable to younger and more liberal residents (Pescosolido et al, 2021). Future interventions might consider ways to capitalize on the lower baseline stigma that may be found in younger generations.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge and attitude of the general public towards people with mental illness differs depending on the type of illness. For example, several studies described a higher propensity for people to maintain a greater social distance from a person with schizophrenia when compared with someone with an anxiety disorder or depression [ 4 , 5 , 6 ]. This tendency was also verified in a study that compared physicians’ attitudes towards people with schizophrenia and depression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%